Pharmaceutical Cocrystals: Regulatory and Strategic Aspects, Design and Development - Dipak Dilip Gadade; Sanjay Sudhakar Pekamwar (Tabriz University of Medical Sciences, 2016)
Cocrystal is a concept of the supramolecular chemistry which is gaining the extensive interest of researchers from pharmaceutical and chemical sciences and of drug regulatory agencies. The prominent reason of which is its ability to modify physicochemical properties of active pharmaceutical ingredients. During the development of the pharmaceutical product, formulators have to optimize the physicochemical properties of active pharmaceutical ingredients. Pharmaceutical cocrystals can be employed to improve vital physicochemical characteristics of a drug, including solubility, dissolution, bioavailability and stability of pharmaceutical compounds while maintaining its therapeutic activity. It is advantageous being a green synthesis approach for production of pharmaceutical compounds. The formation polymorphic forms, solvates, hydrates and salts of cocrystals during the synthesis reported in the literature which can be a potential issue in the development of pharmaceutical cocrystals. The approaches like hydrogen bonding rules, solubility parameters, screening through the CSD database or thermodynamic characteristics can be utilized for the rational design of cocrystals and selection of coformers for synthesis multi-component cocrystals. Considering the significance of pharmaceutical cocrystals pharmaceutical regulatory authorities in the United States and Europe issued guidance documents which may be helpful for pharmaceutical product registration in these regions. In this article, we deal with the design, synthesis, strategic aspects and characteristics of cocrystals along perspectives on its regulatory and intellectual property considerations.